The Role and Impact of Radio Listening Practices in Older Adults’ Everyday Lives - Krause, Amanda E. (Frontiers in Psychology, 2020)
Previous research has indicated older adults value listening to music as a leisure activity. Yet, recent research into listening practices broadly has often focused on younger adults and the use of newer, digital listening technologies. Nonetheless, the radio, which is familiar to older people who grew up with it at the forefront of family life, is important to consider with regard to listening practices and the potential associated well-being benefits. This research investigated older adults’ everyday radio listening practices, in order to begin to understand how the radio fits into their daily lives and how it might influence their sense of well-being. Twenty-five Australian residents (aged 66-87; 56% female, 44% male) participated in semi-structured, one-to-one interviews. The results of a qualitative thematic analysis revealed themes concerning listening preferences, listening routines, access, and motivations/ outcomes. While personal preferences (concerning content, stations, and presenters) were diverse, individuals clearly communicated these as well as their established listening routines and habits. Listener motivations varied: some people focused on the enjoyment that listening to the radio creates while some noted benefits to their well-being, such as relaxation, modifying their mood, and feelings of comfort and community. Radio listening practices can be defined in terms of differing engagement styles, as characterized using continua ranging from passive to active, or focused, listening as well as generalized or specific listening. Based on participants’ experiences, a proposed engagement space model links how people engage with the radio to the possible outcomes mentioned. Importantly, benefits to well-being can result from varied engagement styles. The findings presented provide an in-depth understanding of how the radio fits into older Australians’ everyday life, with implications for considering how the radio might be used as a widely-accessed, low-cost tool for maintaining and enhancing quality of later life.